Research on Prediction of Wear Amount in the Gear Transmission Process Under Complex Working Conditions - Tang Aiwu; Chen Tianyou (Jixie chuandong)
Wear is the main failure form in the gear transmission process. The increased wear will increase the non-linear backlash of the gear teeth, reduce the transmission accuracy and increase the impact force of the tooth surface, which will lead to aggravated vibration of the gear transmission system, and impose great impact on the gear transmission performance and the stable operation of the equipment. In order to solve the above problems, a method for predicting the wear amount in the gear transmission process under complex working conditions is proposed. The gear wear state is identified and determined based on the formal wear index. Through in-depth analysis of the gear wear mechanism, a typical gear wear process curve is drawn based on this, the gear transmission friction torque value is calculated, and a mathematical model of the gear wear amount is built; then the known gear state values are input into the construction model, the predicted gear wear amount is obtained, and the prediction of gear wear amount is realized. The experimental results show that under three complex working conditions, the prediction simulation data proposed in this study is closer to the actual parameters, which fully verifies that the prediction accuracy of the wear amount is higher.